Effect of multiple micronutrient supplementation in pregnant women on infant birth weight - Eny Retna Ambarwati; Hadi Ashar; Ratih Kumorojati; Dwi Yulinda; Nendhy Wahyunia Utami; Reni Tri Lestari (AcTion: Aceh Nutrition Journal, 2023)
The nutritional requirements of pregnant women increase with the gestational age. A low nutritional status is poor for both mothers and infants. Infant birth weight is influenced by nutritional intake during pregnancy. Therefore, multiple micronutrients (MMN) are needed for mothers during pregnancy to prevent low birth weight. This study aimed to determine the effect of MMN on infant birth weight at the Asian Waluyo Jati Clinic. The research method used a quasi-experimental design, with a posttest-only control group design involving 50 pregnant women (25 intervention and 25 control groups). This study was conducted at the Asih Waluyo Jati Clinic, Yogyakarta, in 2022. The intervention group received MMN supplementation starting in the 2nd trimester and standardized prenatal care, whereas the control group received standardized prenatal care throughout pregnancy. Both groups were monitored during the 2nd trimester of pregnancy until delivery. Data were analyzed using the Mann–Whitney U test. The results showed a difference in the mean birth weight of the infants in both groups (1,64 grams). MMN supplementation in the intervention group and standard pregnancy care effectively increased the infants' birth weight by 1,64 grams (p= 0,000). In conclusion, MMN supplementation increased the average birth weight of infants.